Arquitectura del Barroco en el Centro de México - Chávez Domínguez, Sergio (Universidad Autónoma de Ciudad Juárez, 2016)
http://www.uacj.mx/CGTI/CDTE/JPM/Documents/PagProdMult/Paginas%20web/Barroco_verde/Pagina/index.html